A PCS network with correlated arrival process and splitted-rating channels. - Wei Li (IEEE Journal on selected areas in communications)
The arrival of calls (i.e., new and handoff calls) in a personal communications services (PCS) network are modeled by a Markov arrival process (MAP) in which we allow correlation of the interarrival times among new calls, among handoff calls, as well as between these two kinds of calls. Each cell of the network consists of a finite number of channels and a buffer with finite size for handoff calls. There exist some channels among each cell which can be used by splitting the original rate into two channels with different rates if necessary when a handoff call arrives and finds all the channels busy. We obtain the stationary joint probability of number of calls in the cell and the phase of the arrival process, the blocking probability of a new call, the forced termination probability of a handoff call, and the mean dwell time of a handoff call in the buffer. Finally, we obtain the distribution and the mean of the cell's busy period, the distribution and the mean of the first time to split the cth channel, and some other interesting performance measures for the network. Some explicit results for special cases obtained by Lin et al. (see IEEE Trans. Vech. Technol., vol.45, no.1, p.122-30, 1996 and vol.43, no.3, p.704-12, 1994), Tekinary et al. (1992) and by Yoon et al. (1993) can also be directly obtained from the general conclusion. The results presented can provide guidelines for field data processing in PCS network design and performance evaluation